(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Corruption permeates all facets of Nigeria and constitutes a means of perpetrating injustice. This paper examines the phenomenon of corruption and injustice in Nigeria, its various causes as well as some of the negative effects. Using Uche Nnyagu’s At the Centre of No-Man’s Land, this work will explore the various corrupt practices in different dimensions from the so-called police force which is supposed to fight corruption and injustice. In effect, corruption slows growth, leads to inefficient investment in public projects, and slows down foreign investment. This paper explores various forms of injustice in Nigeria, causes and its effect on social needs of the citizens. It also considers some suggestions as regards the way out of injustice in Nigeria.